2019
DOI: 10.1016/j.ssnmr.2019.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Structural description of surfaces and interfaces in biominerals by DNP SENS

Abstract: Biological mineralized tissues are hybrid materials with complex hierarchical architecture composed of biominerals often embedded in an organic matrix. The atomic-scale comprehension of surfaces and organo-mineral interfaces of these biominerals is of paramount importance to understand the ultrastructure, the formation mechanisms as well as the biological functions of the related biomineralized tissue. In this communication we demonstrate the capability of DNP SENS to reveal the fine atomic structure of biomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 64 publications
0
30
0
Order By: Relevance
“…[62] More importantly, it is worth noting that a broadening as well as shifts in some of the NMR resonances were observed on the DNP spectra (in comparison to conventional NMR analyses) ; this was ascribed to the lower temperatures used in the DNP analyses (but without verifying this point by performing a conventional 1 H  13 C CPMAS NMR analysis at 100 K). [81,82] Moreover, differences in DNP enhancements were also noticed for the mineral and organic components of bone (with stronger enhancements for the organic fraction, as shown in Figures 6b-c) ; [81] this implies that future optimizations of the impregnating conditions may also depend on the type of structural information which is sought.…”
Section: Considerations On Sample Preparation For Nmr and Dnp Analysesmentioning
confidence: 95%
See 2 more Smart Citations
“…[62] More importantly, it is worth noting that a broadening as well as shifts in some of the NMR resonances were observed on the DNP spectra (in comparison to conventional NMR analyses) ; this was ascribed to the lower temperatures used in the DNP analyses (but without verifying this point by performing a conventional 1 H  13 C CPMAS NMR analysis at 100 K). [81,82] Moreover, differences in DNP enhancements were also noticed for the mineral and organic components of bone (with stronger enhancements for the organic fraction, as shown in Figures 6b-c) ; [81] this implies that future optimizations of the impregnating conditions may also depend on the type of structural information which is sought.…”
Section: Considerations On Sample Preparation For Nmr and Dnp Analysesmentioning
confidence: 95%
“…[66,89] On the other hand, using DNP, it was shown that a full set of 13 C{ 31 P} REDOR dephasing curves could be recorded on a sheep bone sample in just 11 hours (instead of several weeks in absence of DNP), and this allowed estimating the distance of citrate carbon atoms from the mineral surface. [81] In the latter case, based on these dephasing curves, it was suggested that only two out of three carboxylate functions attach to the mineral surface. This level of information is particularly important in relation to the different computational modeling studies of the organic/mineral interface.…”
Section: Advances In Nmr and Dnp Analyses Of Bone Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic nuclear polarization (DNP) has had a significant impact on solid‐state nuclear magnetic resonance investigations of complex biological systems . With now routine signal enhancements in the 100‐fold range, DNP has aided the in vitro structural studies of amyloid polymers, membrane proteins, and biological material such as collagen, bones and tissues . Improvements in DNP instrumentation, sample preparation, and polarization agent design have also allowed NMR spectroscopists to turn their attention to the cellular environment, where the structural analysis of endogenous concentrations of biological macromolecules has come within reach .…”
Section: Figurementioning
confidence: 99%
“…Dynamic nuclear polarization (DNP) has made significant impact on the solid-state nuclear magnetic resonance (NMR) investigations of complex biological systems. [1][2] With now routine signal enhancements in the 100-fold range, DNP has aided the in vitro structural studies of amyloid polymers, [3][4] membrane proteins [5][6] and biological material such as collagen, bones and tissues [7][8] . Improvements in DNP instrumentation, sample preparation and polarization agent design have also allowed NMR spectroscopists to turn their attention to the cellular environment where the structural analysis of endogenous concentrations of biological macromolecules has come within reach.…”
mentioning
confidence: 99%